A Pulsatile Tablet of Famotidine Using Core in Cup Method. - Shreya Ajay Rajguru; Maimuna Fatima; Hemanth kumar Bandaru; Shaik Farooq Ahmed Ahmed; VIPANCHI Veeranti; Prasanthi Domaraju (IIUM Press, International Islamic University Malaysia, 2023)
Introduction: The present work aims to formulate pulsatile delivery system using "core-in-cup" system for Famotidine, a H2 receptor antagonist used for duodenal ulcer, benign gastric ulcers, GERD and nocturnal acid breakthrough (A physiological condition where there is sudden surge of gastric acidity at midnight). In such situation, pulsatile release of drug is preferable having lag time of 3-4 hrs. Materials and method: Core tablets were prepared by employing direct compression method using HPMC K4M, sodium bicarbonate and MCC. Ethyl cellulose, HPMC K4M and Xanthan gum were used for preparation of Core-in-cup tablets. Results: Pre-compression parameters were within acceptable limits. In-vitro studies indicated core tablet with 40% HPMC K4M showed 85.4± 0.15% drug release at the end of 3hrs. and in-vitro buoyancy indicated formulation remained floating for >3hrs. Thus, 40% HPMC K4M was selected. Drug excipient compatibility studies indicated drug and excipients to be compatible. Prepared core-in-cup tablets were evaluated for hardness (6.0±0.12-7.0±0.12kg/cm2), thickness (3.0±0.15-3.5±0.13mm), weight variation (285±0.20-314±1.06mg), friability (0.53±0.14-0.65±0.12%), floating lag-time (99±0.42-120±0.84sec), swelling index (120±0.56-030±0.60%). In-vitro studies indicated formulations with xanthan gum (F1 & F2) showed lag time of 2±0.12-2.4±0.15hrs and %drug release at the end of 7th hour was 97±0.90% and 90±0.12% respectively. Formulations with HPMC K4M (F3 & F4) showed lag time of 3.5±0.10-4.2±0.18hrs and %drug release at the end of 7th hour was 86±0.34% and 83±0.20% respectively. Model dependent kinetics depicted, F4 follows zero-order release kinetics, 'n' value of korsmeyer-peppas model indicated anomalous transport mechanism, release process being swelling controlled. Optimized formulation was found to be stable for a period of one month. Conclusion: Conventional drug delivery systems of famotidine, cannot be administered when the symptoms start showing. So, oral pulsatile release dosage form i.e., "Core-in-Cup" system possessing gastric retention capabilities was successfully designed such that when given at bed time drug release is seen in morning.